Aluminium droplets combustion and SRM instabilities - Orlandi, Olivier; Plaud, Mathieu; Godfroy, Franck; Larrieu, Severine; Cesco, Nathalie (Acta astronautica, 2019)
This paper presents the effects of the combustion of aluminium droplets in the context of solid propulsion. A focus is made on the specific case of pressure oscillations. After a brief presentation of the characteristics of aluminium combustion, interaction with the acoustics of the motor is introduced. The unsteady phenomenon referred to as ‘ITHAC’ is studied through the analysis of the “Stelis Calypso” test firing. The results show that aluminium combustion is the driving mechanism that leads to a strong instability of several bars. This analysis is supported by numerous two-phase flow simulations that prove the role of aluminium droplets in the triggering of instability characterised by high pressure oscillation levels. A second instability is also addressed. Solid rocket motors are subject to surface vortex shedding (SVS) for which pressure oscillation levels can drastically be modified by aluminium droplets combustion. Depending on the motor geometry and particles size, combustion increases or dampens the hydrodynamic instability and can be considered as an explanation to the pressure oscillations observed during tests of aluminised propellants. •Effects of aluminium droplets combustion on pressure oscillations in solid rocket propulsion.•“Stelis Calypso” firing test investigation to study the interaction of combustion with the acoustic field.•Results show that aluminium combustion is the driving mechanism of a strong instability.•Two-phase flow simulations to prove the role of aluminium droplets in the triggering of instability.•Study of aluminium droplets combustion on surface vortex shedding (SVS).